Aplicação de peroxidases não comerciais extraídas dos farelos de arroz e soja na descoloração de efluentes - Marques, Camila Torbes (2016)
This study investigated the use of non-commercial peroxidases extracted from by-products of agro-industrial activities (rice and soy bran) in the discoloration of a synthetic effluent, which used a textile dye in its composition. To this, the enzymes were subjected to contact with the effluent in an orbital shaker using different conditions in order to evaluate the optimum concentration of hydrogen peroxide (H2O2) and the optimum volume of enzymatic extract for the discoloration reaction, by the use of experimental design methodology. It was necessary to add H2O2 to start the discoloration reaction because the enzyme peroxidase depends on H2O2 to become active. The use of peroxidase enzyme extracted from rice bran (AT: 27.25 U/mL) when in contact with the synthetic effluent resulted in approximately 46% color removal when larger volumes of enzyme extract (15 mL) in smaller concentrations of H2O2 (20 and 40 mg/L) were used in 5h reaction. For the peroxidase extracted from soybean bran, satisfactory results were not obtained for the discoloration of the synthetic effluent. From the obtained results, other parameters of the synthetic effluent were also analyzed in order to investigate the changes that occurred in it due to the enzymatic treatment. It was possible to observe at the end of the process, that besides color removal, the temperature was in the environment range (25°C), pH of around 7, the turbidity was reduced by approximately 36%, total and fixed solids were found in lesser amounts and the residual H2O2 concentration was only 0.5 mg/L. The data from this study suggest that the peroxidase enzyme obtained from a non-commercial source (rice bran) has potential in effluents discoloration, since its obtaining process is easy and economically viable when compared to its commercial source. In this context, the study is extremely relevant, since due to the high cost of commercial enzymes, more and more it is necessary to discover other cheaper enzyme sources, which might be promising alternatives to conventional wastewater treatment.